2014
DOI: 10.4028/www.scientific.net/amr.919-921.1115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Large Track Maintenance Machine on Sleeper Supporting Stiffness

Abstract: Large track maintenance machine is one of the most important components of modernization of rail technical equipment. The sleeper supporting stiffness after large track maintenance operation has an effect on the safety and stability of train operation. This article make some conclusions through the analysis the influence of large track maintenance machine operation on sleeper supporting stiffness. It is indicated that during the maintenance operation, ballast compactness is enhanced and the supporting stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The relationship of several loading cycles and settlement was found, which indicated that the initial settlement process and rate of residual settlement alter after 30% sand. The study (Zhang et al 2014) considered the influence of large track maintenance machine operation on sleeper supporting stiffness. It is indicated that during the maintenance operation, ballast compactness is enhanced, and the supporting stiffness increases by the tamping process.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of several loading cycles and settlement was found, which indicated that the initial settlement process and rate of residual settlement alter after 30% sand. The study (Zhang et al 2014) considered the influence of large track maintenance machine operation on sleeper supporting stiffness. It is indicated that during the maintenance operation, ballast compactness is enhanced, and the supporting stiffness increases by the tamping process.…”
Section: Introductionmentioning
confidence: 99%